1989
DOI: 10.1182/blood.v74.1.395.bloodjournal741395
|View full text |Cite
|
Sign up to set email alerts
|

Two regression models and a scoring system for predicting survival and planning treatment in myelodysplastic syndromes: a multivariate analysis of prognostic factors in 370 patients

Abstract: Therapy planning in patients with myelodysplastic syndromes (MDSs) is complicated by its high prognostic heterogeneity. Forty-one patient and disease characteristics at onset of 370 patients with MDS were analyzed to identify significant prognostic factors for survival and transformation to acute myeloblastic leukemia (AML), and to develop and validate a regression model for predicting survival. Multivariate regression analysis showed that the total bone marrow percentage of blast cells, age, platelet count, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
60
1
8

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 0 publications
3
60
1
8
Order By: Relevance
“…According to the Kaplan-Meier estimates, the median survival of patients with RAEB I was 16 months, as compared with 9 months in patients with RAEB II (P ¼ 0AE0031). This is in line with other smaller series (Sanz et al, 1989;Germing et al, 2000;Nosslinger et al, 2001;Lee et al, 2003;Lorand-Metze et al, 2004). Similarly, the risk of developing overt AML was significantly greater for patients with RAEB II versus RAEB I. Irrespective of the RAEB subgroup, there were four independent prognostic parameters for survival, namely age >70 years, haemoglobin concentration <10 g/dl, platelet count <100 · 10 9 /l and a proportion of more than 10% blasts in the bone marrow.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…According to the Kaplan-Meier estimates, the median survival of patients with RAEB I was 16 months, as compared with 9 months in patients with RAEB II (P ¼ 0AE0031). This is in line with other smaller series (Sanz et al, 1989;Germing et al, 2000;Nosslinger et al, 2001;Lee et al, 2003;Lorand-Metze et al, 2004). Similarly, the risk of developing overt AML was significantly greater for patients with RAEB II versus RAEB I. Irrespective of the RAEB subgroup, there were four independent prognostic parameters for survival, namely age >70 years, haemoglobin concentration <10 g/dl, platelet count <100 · 10 9 /l and a proportion of more than 10% blasts in the bone marrow.…”
Section: Discussionsupporting
confidence: 89%
“…However, their prognosis is very heterogeneous with respect to survival and risk of leukaemic transformation, probably as a result of the wide range of medullary blast counts. After Spanish investigators had identified this as a shortcoming of the FAB classification (Sanz et al, 1989), several studies underscored the prognostic importance of blast counts (De Rosa et al, 1987;Michels et al, 1989;Chevret et al, 1994;Guerci et al, 1995;Ohyashiki et al, 2001;Strupp et al, 2003). These findings were taken into consideration when a working party of the World Health Organization (WHO) proposed a revised classification of neoplastic diseases of the haematopoietic and lymphoid tissues (Harris et al, 1999).…”
mentioning
confidence: 99%
“…The IPSS (Greenberg et al, 1997) is widely used and incorporates bone marrow blast percentage, bone marrow cytogenetics and number of lineages with cytopenia to provide prognostic information. The IPSS follows on from other prognostic scoring systems that are similar, in so much as they all require bone marrow aspirate ± cytogenetic analysis (Mufti et al, 1985;Sanz et al, 1989;Aul et al, 1992;Morel et al, 1993). Bone marrow aspirate and cytogenetics are commonly, but not always, used in the diagnosis of MDS and may not be required when a definitive diagnosis of MDS would not alter management, for example, in the elderly (Bowen et al, 2003) -the age group with the highest incidence of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…8 With regard to MDS, transformation into AML occurs in 6±37% of patients. 13 Byrd et al 4 reported that leukaemia cutis and granulocytic sarcoma have rarely been seen in patients with MDS, with only 46 patients previously described, and that 32 cases occurred in the absence of AML. Among these 32 cases, AML developed in 47% at a mean of 38 weeks after the initial diagnosis of granulocytic sarcoma.…”
Section: Discussionmentioning
confidence: 99%